Research recommendations following the discovery of pain sensitizing IgG autoantibodies in fibromyalgia syndrome - Goebel, A; Andersson, D; Barker, C; Basu, N; Bullock, C; Bevan, S; Bashford-Rogers, RJM; Choy, E; Clauw, D; Dulake, D; Dulake, R; Flor, H; et al. (Oxford University Press, 2021)
Background Fibromyalgia syndrome (FMS) is the most common chronic widespread pain condition in rheumatology. Until recently, no clear pathophysiological mechanism for fibromyalgia had been established, resulting in management challenges. Recent research has indicated that serum immunoglobulin Gs (IgGs) may play a role in FMS. We undertook a research prioritisation exercise to identify the most pertinent research approaches that may lead to clinically implementable outputs.